Penerapan Application Programming Interface (API) Pada Push Notification Untuk Informasi Monitoring Stok Barang Minim - Anggra Triawan; Andika Ramot Yesaya Siboro (Sekolah Tinggi Ilmu Komputer Binaniaga, 2021)
Technological advances along with the times are getting more targeted and easier in everyday life, one of which is in industrial companies. In every industrial company there is a purchasing department whose job is to make purchases of goods if the stock of goods is running low. But the Purchasing section always has difficulty controlling the minimal stock of goods that are so many in the company, so that there are often delays in purchasing goods, this is due to the ineffectiveness of the process of delivering information about minimal stock data from both the raw material warehouse and from the existing system. In this research, a prototype is made to be a solution to existing problems, where the Application Programming Interface (API) will be able to become a liaison between existing systems and other systems that will send push notifications in sending information about stock data that has reached the limit. minimal when the transaction process is still going on, so as to reduce the level of delay in purchasing goods as a result of the ineffectiveness of notification of information regarding the minimum stock of goods that has occurred so far. A feasibility test has been carried out on the prototype that was built, with a feasibility value of 71% which means that the prototype built is feasible and has also been tested for accuracy using the Field Observation Method with 80% effectiveness results.